MORPHEME AND METONYMY - G'aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
This article discusses the types of of transfer of meaning that is, metomymy metaphor . how to distinguish between them and a guide to some excerses for a broader understading of this topic